The Effect of Reminiscence Therapy on The Level of Anxiety for Elderly People - Indarwati, Retno; Fauzi, Abdul; Asmoro, Candra Panji; Asmoro, Candra Panji (International Journal of Psychosocial Rehabilitation, 2020)
The amount of anxiety was increased in the elderly person. The anxiety was caused by several factors, and there were elderly internal factors and the environment. Anxiety had a negative impact on the elderly’s life. One of the non-pharmacological therapy that can be used to treat anxiety was reminiscence therapy. Reminiscence therapy was an intervention that memorizes a beautiful experience. This research was aimed to determine the effect of reminiscence therapy to reduce the elderly’s anxiety level. This research used Pre-Experimental One Group Pre-Post Test design. The population of this research was 20 elderly who experience anxiety. This research used a total sampling technique. The number of respondents in this study was 20 respondents. The independent variable in this research was reminiscence therapy, and the dependent variable was the level of anxiety. Data were collected using the Zung Self-Rated Anxiety Scale (ZSAS) questionnaires which consisted of 20 questions. The anxiety levels were analyzed by using the Wilcoxon signed- rank test, with a level of significance α<0.05. The results showed that reminiscence therapy influenced the anxiety level with a significant level of p=0.000. This reminiscence therapy could reduce the anxiety level of the elderly. This therapy was recommended as one of the options that can be used modality therapy in the elderly who experience anxiety